2021
DOI: 10.1016/j.fct.2021.112262
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce sodium levels in European seabass sausages

Abstract: Considering the increasing demand towards "ready-to-cook" processed seafood products, recognised as being potential contributors to high Na intake by consumers, this study aimed to assess the effect of sodium chloride (NaCl) reduction on physicochemical, microbiological and sensory properties of European seabass (Dicentrarchus labrax) sausages stored in chilling conditions during 5 weeks. Three formulations were tested in comparison with a control (100% NaCl, CTR): (i) 50% NaCl+50% ME (oleoresins microcapsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Therefore, the fish colour was not affected (in general) by the brine and formulation (NaCl replacement by KCl). Similar results were observed for Na-reduced smoked salmon and seabass sausage [14,41].…”
Section: Colour and Texturesupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, the fish colour was not affected (in general) by the brine and formulation (NaCl replacement by KCl). Similar results were observed for Na-reduced smoked salmon and seabass sausage [14,41].…”
Section: Colour and Texturesupporting
confidence: 85%
“…The texture analysis was carried out using a TA.XTplus analyser (Stable Micro Systems, Surrey, UK); the Texture Profile Analysis (TPA, double compression test) was performed using a 30 kg load cell and an aluminum compression plate of 75 mm diameter (P75). The highest part of both fillets (part 3a in Figure 2) was cut into 20 × 20 mm cubes (one per fillet), which were compressed twice by up to 60% of the original height (12-15 mm) at a constant speed of 1.00 mm/s [14]. The primary characteristics obtained included hardness (maximum force of the compression), springiness (distance of the height detected during the second compression divided by the original compression distance) and cohesiveness (area of work during the second compression divided by the area of work during the first compression).…”
Section: Texturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the results indicated that juiciness decreased but not significantly. Similarly, Claus and Hunt [ 41 ] reported a decrease in juiciness due to the use of starch. This decrease in juiciness may have been due to the fact that TS bonded strongly with water and subsequently, caused the sausage to appear dry to panellists.…”
Section: Resultsmentioning
confidence: 97%
“…The scores provided by the taste panellists for saltiness were significantly ( p < 0.05) reduced with each treatment reduction in NaCl concentration. Estevez et al [ 41 ] also found that NaCl concentration directly influenced saltiness in seabass sausages. The fact that there were no sensory changes following the addition of KCl\TS suggests that when NaCl concentration was substituted with KCl, the concentration used may have been too low to have had an effect on the perceived saltiness of the sausages.…”
Section: Resultsmentioning
confidence: 99%